Peningkatan Pengetahuan dan Perubahan Sikap Masyarakat Kutalimbaru Terhadap Autopsi melalui Pengabdian Masyarakat - Petrus, Asan (Jurnal Pengabdian Masyarakat dan Penerapan Ilmu Pengetahuan, 2025)
Kutalimbaru Subdistrict is one of 22 subdistricts in Deli Serdang Regency, with an area of 174.92 km² and a population of 36,450. Previous studies indicate that this region continues to face crime-related issues, including gambling, which may result in fatalities and highlight the critical role of forensic medicine in determining the cause of death through autopsy. However, in practice, many community members still reject autopsy due to limited understanding of its purpose and benefits, thereby hindering legal processes. This community engagement program in Kutalimbaru aimed to improve local knowledge and attitudes toward autopsy in cases of unnatural death. The intervention involved screening real case videos, delivering lectures on the definition, objectives, and benefits of autopsy, and distributing pre-test and post-test questionnaires to measure changes in participants’ knowledge and attitudes. The activity was conducted with approximately 60 members of a local women’s religious study group (majelis taklim). Results showed an increase in knowledge scores from 60 to 80, accompanied by a more open and supportive attitude toward autopsy as part of ensuring justice. Discussions were interactive, particularly concerning legal aspects, prevailing myths, costs, and locations of autopsy. Overall, this program proved effective in enhancing forensic literacy and preparing communities to accept autopsy as an essential component of law enforcement, with recommendations for similar programs to be sustained and expanded with additional health-related topics in comparable settings.